The bloomsbury handbook of bourdieu and educational research - Stahl, Garth; Mu, Guanglun Michael; Ayling, Pere; Weininger, Elliot B. (Bloomsbuury Academic, 2024)
This book is the first international reference work to showcase the diversity of ways of using Bourdieu's sociological toolkit in educational research. Written by scholars based in Australia, Brazil, Canada, China, Indonesia, Hong Kong, the UK, and the USA, the handbook provides a unique and cutting-edge picture of how Bourdieu has been both used and adapted in educational research globally. The book will be useful for those who may only have a cursory knowledge of Bourdieu's tools as well as those who are already familiar with Bourdieu's work. The chapters cover a wide range of topics including educational leadership, teacher preparation, space/place, educational policy, literacy education, marginalised students, and student mobility